The Mortality Crisis in East Germany - Klaus F. Zimmermann; Regina T. Riphahn (Institute for the Study of Labor (IZA), 1998)
A number of studies suggest that mortality rates among East German men increased in the wake of reunification, in particular between 1989 and 1991, in some age groups by up to thirty percent. This study first examines the developments of mortality and cause of death statistics based on detailed regional data. The results indicate that there was indeed an increase in mortality rates which cannot be dismissed as a statistical artefact. Next, the paper discusses various theories explaining mortality crises and their relevance for the case of East Germany. Based on individual-level panel data the relationship between exposure to stress and overall health is shown. Apparently, the increase in mortality can be explained by the increase in individual stress levels after the economic, cultural and political consequences of reunification.
Keywords: I12; J11; 330; mortality; stress; transition; East Germany; Sterblichkeit; Männer; Streß; Neue Bundesländer; Nationale Einheit; Deutschland